Needs Assessment for Online Health Education on Diabetes during Covid-19 Pandemic - et al., Emy Leonita (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Indonesia is in the 6th rank for the highest number of people with diabetes in the world. In fact, diabetes is one of the most common predictors of morbidity in Covid-19 patients. The current condition of Covid-19 pandemic hampers the management of diabetes because of limited patient access to health services. One of the efforts needed for diabetes management is health education. This study aims to obtain information about the readiness of community to take advantage of online education and online educational media which are needed during Covid-19 pandemic. It utilized mix method including quantitative and qualitative methods. Data were collected using a questionnaire distributed via google form to 140 community in-depth interviews with a leader of public health center. The community also need online education in videos and pictures accompanied by online discussion forums with doctors. the strongly agree and agree percentage is required, the online educational media that mostly used by the community was WhatsApp. Health workers also needed online educational media during Covid-19 pandemic.